Employed but Still Poor: The Condition of Working Poor Households in Central Java, Indonesia - Dinar Melani Hutajulu; Fitrah Sari Islami; Andhatu Achsa; Ivo Novitaningtyas (Integrated Journal of Business and Economics (IJBE), 2026)
This study aims to chart the spread of working poor individuals across Central Java, based on the province's actual conditions, to determine if employment alone can help the population escape poverty, and to identify the factors that enable poor workers in Central Java to lift themselves out of poverty. This study utilizes data from the 2023 National Socio-Economic Survey, specifically for Central Java Province, which includes a sample of 51,881 workers. Data analysis was conducted using logistic regression, the results of which reveal that the districts of Blora and Grobogan exhibit the highest proportions of working poor individuals in the entire province. Having a job is insufficient on its own to avoid poverty; a combination of additional elements and criteria is necessary for an individual to maintain a satisfactory standard of living and avoid financial difficulties. Demographics, employment status, household circumstances, and location all have a statistically significant impact on a worker's prospects of overcoming poverty, with the exception of individuals aged over 60 years. Relevant government authorities and local stakeholders may implement various regulatory measures and policy initiatives, such as worker welfare programs, aligning education with labor market needs, promoting digital infrastructure, offering micro-enterprise incubation services, developing inclusive financial access, expanding social protection to cover informal sector workers, improving rural areas, encouraging diversified economic activities in villages, and enhancing connectivity between rural and urban areas throughout Central Java.